The Validity and Between-Unit Variability of GNSS Units (STATSports Apex 10 and 18 Hz) for Measuring Distance and Peak Speed in Team Sports - Beato, Marco; Coratella, Giuseppe; Stiff, Adam; Iacono, Antonio Dello (Frontiers in Physiology, 2018)
The aims of this study were (i) to investigate the criterion validity (vs. gold standard measurements) of the 10 and 18 Hz STATSports Apex units for measuring distances and peak speed (Vpeak) outcomes; (ii) to investigate the between-unit variability. Twenty university students were enrolled in the study (age 21 ± 2 years, weight 72 ± 6 kg, height 1.76 ± 0.05 m). The criterion validity was tested by comparing the distances recorded by the units with ground truth reference (400-m trial, 128.5-m circuit and 20-m trial). Vpeak values were compared with those determined by a gold standard criterion device (Stalker ATS Radar Gun) during a linear 20-m sprint. The distance biases for the Apex 10 Hz in the 400-m trial, 128.5-m circuit and 20-m trial were 1.05 ± 0.87%, 2.3 ± 1.1%, and 1.11 ± 0.99%, respectively, while for the Apex 18 Hz the biases were 1.17 ± 0.73%, 2.11 ± 1.06%, and 1.15 ± 1.23%, respectively. Vpeak measured by the Apex 10 Hz and Apex 18 Hz were 26.5 ± 2.3 km.h-1 and 26.5 ± 2.6 km.h-1, respectively, with the criterion method reporting 26.3 ± 2.4. km.h-1, with a bias of 2.36 ± 1.67% and 2.02 ± 1.24%, respectively. This study is the first to validate and compare the STATSports Apex 10 Hz and 18 Hz. Between-analysis (t-test) for total distance and Vpeak reported non-significant differences. Apex units reported a small error of around 1-2% compared to the criterion distances during 400-m, 128.5-m circuit, 20-m trials and Vpeak. In conclusion, both units could be used with confidence to measure these variables during training and match play.